2014
DOI: 10.1111/jerd.12117
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of a CAD/CAM Prosthesis for Immediate Defect Repair after Total Maxillectomy: A Case Series of 18 Patients with Maxillary Sinus Cancer

Abstract: This surgical treatment of maxillary sinus cancer is applied rarely in China, but it has a good effect based on our observation. Simultaneous CAD/CAM prosthesis implantation after total maxillectomy can recover the facial profile, enhance the speaking, swallowing, and chewing functions, and improve the quality of life of patients. Tumor recurrence can be detected by direct observation of the postoperative maxillary cavity. This technique avoids the need for dental implants because the bottom part of the prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…The results of occlusal force measurements were more convincing at this time. Our data were also consistent with Jiang et al and evidences that the recovery of occlusal forces in the 6 months post‐operatively is valuable. Ma indicated that a complete denture could restore 15%‐25% of the occlusal force of natural dentition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of occlusal force measurements were more convincing at this time. Our data were also consistent with Jiang et al and evidences that the recovery of occlusal forces in the 6 months post‐operatively is valuable. Ma indicated that a complete denture could restore 15%‐25% of the occlusal force of natural dentition.…”
Section: Discussionsupporting
confidence: 93%
“…Murakami et al reported that the improvement of masticatory functions and the QoL is associated with the improvement in participants' occlusal force. Jiang et al reported that the completion of jaw reconstruction takes 6 months after operation, and the occlusal relationship stabilises after the replacement of the permanent prosthesis. The results of occlusal force measurements were more convincing at this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxillofacial reconstruction surgery focuses on rebuilding the original shape of the affected region [20]. All functions of the upper jaw-including ventilation through the paranasal sinus system, chewing, biting, and swallowing-are associated with the original shape of the maxillary bone [20,21]. Maxillary and zygomaticomaxillary complex fracture reduction focuses on restoring the malar prominence, zygomatic arch, and maxillary buttresses [22].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid prototyping technology, better known as 3-dimensional (3D) printing, is widely used for preoperative planning, procedure rehearsal and custom prosthetic design in clinical practice as well as an educational tool for teaching and to enhance communication between the patient and doctor [ 2 , 3 ]. In dentistry, 3D printing technology is currently used in implant surgery [ 4 , 5 ], oral and maxillofacial surgery [ 6 , 7 ], orthognathic surgery [ 8 , 9 ], prosthodontics [ 10 , 11 ] and endodontics [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%